Using comparable corpora for under-resourced areas of machine translation - Skadiņa, Inguna; Gaizauskas, Robert; Babych, Bogdan; Ljubešić, Nikola; Tufiş, Dan; Vasiļjevs, Andrejs (Springer International Publishing, 2019)
This book provides an overview of how comparable corpora can be used to overcome the lack of parallel resources when building machine translation systems for under-resourced languages and domains. It presents a wealth of methods and open tools for building comparable corpora from the Web, evaluating comparability and extracting parallel data that can be used for the machine translation task. It is divided into several sections, each covering a specific task such as building, processing, and using comparable corpora, focusing particularly on under-resourced language pairs and domains. The book is intended for anyone interested in data-driven machine translation for under-resourced languages and domains, especially for developers of machine translation systems, computational linguists and language workers. It offers a valuable resource for specialists and students in natural language processing, machine translation, corpus linguistics and computer-assisted translation, and promotes the broader use of comparable corpora in natural language processing and computational linguistics
Keywords: Ähnlichkeit; Korpus; Maschinelle Übersetzung